Formation of potential foreign language teachers' research competence at the university as a condition for the modernisation of education - M. M. Mombekova (Russian State Vocational Pedagogical University, 2024)
Introduction. The investigation of student research competence development, closely related to the issues of organising educational and scientific research activities in the university environment, is an urgent problem in higher education. Aim. The aim of the research is to theoretically substantiate and develop a model for the formation of research competence in potential foreign language teachers and to create conditions for its implementation in the university environment. Methodology and research methods. The study was founded on a methodological framework rooted in competent-based, active engagement, systematic, humanitarian, and axiological approaches. Analysis, synthesis, generalisation, comparison, experimentation, questionnaires, observations and statistical analysis were employed to establish the foundation of the research. Results and scientific novelty. The concept of "research competence" and its structural components are specified and identified as: motivational-personal, cognitive, behavioural, constructive-designing, transmissive, and reflective-evaluative. The authors have scientifically substantiated and tested a model for the development of research competence in future teachers of a foreign language. This model aims to develop the main research skills of students and includes motivational-personal, cognitive, behavioural, constructive-designing, transmissive, and reflective-evaluative components. Practical significance. The research findings can be used for organising educational and research work among various categories of participants, such as students, undergraduates, and foreign language teachers. Educational courses built upon this model can be seamlessly integrated into the curriculum as an independent module dedicated to the preparation of future foreign language teachers.